Homology Modeling Of β-Glucuronidases From E. Coli and T. Maritima - Noorbatcha, Ibrahim Ali; Masrur Khan, Ayesha; Mohd. Salleh, Hamzah (Universiti Malaya, 2009)
The enzyme β-Glucuronidases (GUS) which belongs to the glycoside hydrolase family of enzymes, can hydrolyze any aglycne conjugated to D-glucuronic acid through a β-O~glycosidic linkage. It is present in almost all tissues of vertebrates and their residentinal flora, including E. coli. However, GUS enzymes obtained from different sources have different stability towards heat, resistance to detergents and varying catalytic activities. A good understanding or the reasons for this variation can lead to designing new enzymes with desired level of property. having great prospect in the industry. For this purpose, studies on the three-dimensional structure of GUS enzyme can offer insights on the structure-function correlations, and provide information on the distribution or certain residues both in E. coli and T. maritima enzymes. The structures of GUS enzymes from E. coli and T. maritima are not known experimentally. As such in the current work, homology modeling or the three-dimensional structure of both variants of the GUS enzyme was carried out based on the solved crystal structure of Human GUS enzyme. Multiple sequence alignment for both enzyme sequences was carried out in order to locate the most suitable template for homology modeling and the models thus prepared were found to cotain 32-43% sequence identity with the template. Superposition of the model obtained with the template as well as structural alignment were carried out to classify the structural differences. This paper will also present an analysis and verification studies of the model based on various criteria. The current work offers a better understanding of the structural differences between GUS enzymes from different sources, as well as suggests regions for further modification using experimental and computational methods.